Complementarity of PALM and SOFI for super-resolution live-cell imaging of focal adhesions - Hendrik Deschout (Nature Portfolio, 2016)
Live cell super-resolution imaging requires a high temporal resolution, which remains a challenge. Here the authors combine photo-activated localization microscopy (PALM) with super-resolution optical fluctuation imaging (SOFI) to achieve high spatiotemporal resolution and quantitative imaging of focal adhesion dynamics.